Markers of Sleep-Disordered Breathing and Prediabetes in US Adults - Alshaarawy, Omayma (Hindawi Publishing Corporation, 2012)
Background. Prediabetes is a preclinical stage in the hyperglycemia continuum where subjects are at increased risk of developing diabetes. Several studies reported a positive association between markers of sleep-disordered breathing (SDB) and diabetes. However, few studies investigated the relationship between SDB markers and prediabetes. Methods. We examined 5,685 participants ≥20 years from the National Health and Nutrition Examination Survey (NHANES) 2005–2008. The exposure of interest was SDB markers including sleep duration, snoring, snorting, and daytime sleepiness. The outcome was prediabetes (n = 2058), among subjects free of diabetes. Results. SDB markers were associated with prediabetes. Compared to those without any sleep disturbance, the multivariable odds ratio (OR) (95% confidence interval (CI)) of prediabetes among those with three or more SDB markers was 1.69 (1.28–2.22). In subgroup analyses, the association between SDB markers and prediabetes was stronger among women (OR (95% CI) = 2.09 (1.36–3.23) when compared to men (1.52 (1.00–2.35)) and was present among non-Hispanic whites (2.66 (1.92–3.69)) and Mexican Americans (1.99 (1.13–3.48)), but not among non-Hispanic blacks (1.10 (0.70–1.73)). Conclusion. SDB markers were associated with prediabetes. This association was stronger in women and was present mainly in non-Hispanic whites and Mexican Americans.